The structure of void space of complex structured Bashkir carbonate reservoir rocks from the Opishnianske deposit of the DDD - S. Vyzhva; I. Bezrodna; O. Tkachenko (Геофизический журнал, 2019)
The analysis of materials of well-logging of the wells of the Opishnanske deposit of the DDD was conducted for the purpose of the determination of their reservoir promise. The void structure of Bashkir carbonate reservoir rocks (productive horizon B-10) of 11 wells of the Opishnanske deposit of the DDD was defined for the first time in this article. The quantitative assessment of porosity types of reservoir rocks was done using a method, developed at the Taras Shevchenko University of Kyiv, which basis is a complex of well-logging methods that includes radioactivity and acoustic logging. Using well-logging methods, the potential reservoir rocks were distinguished, the forms of voids were calculated, and the contribution of different void types (intergranular, fracture, vuggy, secondary porosity) in the absolute porosity was assigned. As a result of the study, it was found that the fracture voids are present to a large extent only in layers, presented by water-saturated reservoir rocks, whose fracture porosity ratio acquire values from 0,2 % to 1,5 %. The fracture type of voids is present in layers with gas-saturated reservoirs in rocks with considerably lower concentrations (from 0,05 to 0,29 %). The vugggy voids are distinguished in almost a majority of layers, a vuggy porosity ratios in them reach 9,8 %. Based on the determination of type and concentration of voids in car-bonate reservoir rocks, the promise and predictive discharges of water and gas were determined by authors using a calculated parameter of the unit surface area of voids. The authors have identified the predictive yields higher than 1tonn per day in all wa-ter-saturated reservoir layers, and the highest were in two layers with daily flowrates of 307 and 3200 t/d in the well intervals of: 2816,4—2820 m (№ 12) and 2864—2870,4 m (№ 114). The highest predictive discharge of gas, that is 352 thousand cubic meters per day, is determined in a well 127 (the interval of 2773,8—2775,5 m). The gas discharges in three intervals of the well 127 are calculated within 140 thousand cubic meters per day (2762,4—2764,7, 2788—2790, 2822,8—2824,4 m). Increased discharges correlate with the presence of fracture and increased secondary porosity.